012 Evaluation of Antibiotic Metaphylactic Therapy for Receiving Calves at Risk for Bovine Respiratory Disease. (1st February 2016) - Hawley, J.; Powell, J. G.; Kegley, E. B.; Beck, P. A.; Reynolds, J. L.; Hornsby, J. A.
Abstract: Metaphylactic antimicrobial therapy is one strategy used to mitigate the risk of developing bovine respiratory disease (BRD ) in newly received stocker cattle. The objective of this study was to evaluate the efficacy of single dose metaphylactic ceftiofur crystalline free acid ([Excede ] 6.6 mg/kg BW; Pfizer Animal Health, Exaton, NY) or tilmicosin phosphate ([Micotil ] 13.3 mg/kg BW; Elanco Animal Health, Indianapolis, IN) on measures of performance and animal health in receiving calves at risk for BRD. A total of 303 crossbred bull (n = 39) and steer (n = 264) calves (initial BW = 211 ± 12.6 kg) were received on 3 dates. Calves were stratified to pens by castrate status and body weight. Castrate status was equally distributed to treatments by assigning a similar number of bull and steer calves to each treatment pen (8 pens per block). Pens were then assigned randomly to single dose antimicrobial metaphylaxis: 1) Excede or 2) Micotil. No differences ( P ≥ 0.23) in ADG were observed between antibiotic metaphylactic treatments (1.2 vs 1.23 ± 0.04 kg/d, respectively). There was a trend ( P = 0.13) for morbidity (calves treated at least once for BRD) rates to differ between metaphylactic treatments, with calves receiving Excede more likely to be treated for BRD (19.9 vs. 15.1%, respectively). Similarly, cattle receiving Excede required 80% more second ( P = 0.05; 11.9 vs. 6.6%, respectively) and 400% more third ( P = 0.01; 6.6 vs. 1.3%, respectively) antibiotic treatments. However, the average days from arrival until first ( P = 0.10) and second ( P = 0.05) treatments for BRD were increased for the Excede calves when compared to the Micotil calves. Metaphylactic treatment did not affect ( P ≥ 0.16) subsequent BRD treatment success (calves treated initially for BRD that did not require a second antibiotic treatment and calves treated with second antibiotic that did not require a third antibiotic treatment). The reduction in BRD morbidity rate for Micotil calves tended to result in fewer ( P = 0.07; 0.38 vs. 0.23 antibiotic treatments for clinical BRD/calf, respectively) antibiotic treatments per calf and 5.62/calf less ( P ≤ 0.05) total antibiotic costs. Based on these results Micotil was more cost effective and efficacious as metaphylactic therapy for BRD in receiving calves at risk for disease.